Declining Wage Inequality in Developing Countries: The Case of Brazil - Firpo, Sergio; Portella, Alysson (Journal of Economic Literature, 2025)
Despite rising inequality in rich countries, many developing economies have experienced a decline in inequality in recent decades. Brazil is a notable example. From 1995 to 2015, its Gini index decreased from 58 to 48 points. An extensive body of research has investigated a diverse set of explanations for this reduction. This article reviews this literature, using Brazil as a privileged case study to understand the broader phenomenon of inequality decline in many parts of the developing world. We present stylized facts about inequality during this period, focusing on the results of decomposition methods. We then examine research that employs quasi-experiments and structural models to assess mechanisms related to labor supply and demand, trade, technological changes, and institutional factors such as the minimum wage and race and gender discrimination. We end by discussing some unanswered questions. (JEL D31, D63, J22, J23, J31, O15)